PENGARUH PENGALAMAN KERJA, TINGKAT PENDIDIKAN DAN PELTIHAN TERHADAP KINERJA KARYAWAN PT SEMEN BATURAJA (persero) Tbk DI DIVISI OPERATION - Edi Susanto; Jefirstson Richset Riwu Kore; Juhaini Alie (Fakultas Pertanian, 2022)
This study aims to analyze and prove the effect of work experience, level of education and training on the performance of employees of PT Semen Baturaja (Persero) Tbk in the Operations Division, both partially and simultaneously. The population of this study is 286 employees of PT Semen Baturaja (Persero) Tbk in the Operations Division with a sample of 127 employees. The sampling technique used is Non-probability sampling with the type of sampling that is purposive sampling. The results showed that the t value of the work experience variable (4.204) > ttable (1.97944), the t-count value of the education level variable (4.218) > t table (1.97944), the t-count value of the training variable (6.067) > ttable (1 .9746) and calculated F value (65.117) > F table (2.68). The correlation coefficient (R) 0.783 shows a strong and positive relationship, the coefficient of determination (R2) is 0.614 which means 61.4% of the employee performance variables of PT Semen Baturaja (Persero Tbk in the Operations Division can be explained by the variables of work experience, level of education and training and 38 ,6% is influenced by other variables.The conclusion of this study shows that the variables of work experience, level of education and training partially and significantly have a positive and significant influence on employee performance.